Relationship Between Food and Nutrition Literacy and Caring Behavior about Food and Nutrition among Caregivers of Children Aged 3-5 Years - Thanormchayathawat, Benjawan; Wiriyasirikul, Napawan; Muksing, Witchuta; Wiriyasirikul, Suwichaya; Hemthanon, Sutut; Pum-iem, Thaworn (Princess of Naradhiwas University Journal, 2025)
This descriptive research study aimed to examine the relationship between food and nutrition literacy and caring behavior about food and nutrition among caregivers of children aged 3-5 years. Samples were 174 caregivers of children aged 3-5 years in Tha Ruea subdistrict, Mueang district, Nakhon Si Thammarat province by using simple random sampling. Instruments were a food and nutrition literacy questionnaire and a questionnaire assessing caring behavior about food and nutrition among caregivers. The content validity indices were 0.95 and 0.86, respectively. Data were analyzed by using frequency, percentage, average, standard deviation, and Pearson’s Correlation Coefficient. The findings showed that food and nutrition literacy was at a suitable level (36.2%), caring behavior about food and nutrition was at a moderate level (52.3%). There was a strong statistically significant positive correlation between food and nutrition literacy and caring behavior about food and nutrition among caregivers of children aged 3 - 5 years at .01 (r = .516 p = .00). Regarding the component, it was discovered that accessing information about food and nutrition, developing an understanding of that information, asking for information about food and nutrition, making decisions about food and nutrition, and bringing food and nutrition literacy to apply had statistically significant relationships with caring behavior about food and nutrition at 0.1 (r = 0.379, 0.503, 0.436, 0.493, 0.439, p = 0.00), respectively. The caregiver is a crucial person in caring about food and nutrition for children. As a result, this research should serve as a guideline for raising food and nutrition literacy in order to encourage responsible behavior that leads to healthy nutrition for children.